Analysis of Turkish Translations of Snow White by the Brothers Grimm In the Context of the Skopos Theory - Uğur Cansız; Lokman Tanrıkulu (Studien zur Deutschen Sprache und Literatur)
Fairy tale is a literary genre, particularly appealing to children and favored by them for reading. In this study, within the framework of Skopos theory, translations of the fairy tale Snow White by Wilhelm Carl Grimm and Jacob Ludwig Carl Grimm were examined. These authors are prominent figures in the realm of fairy tales both in Europe and in Turkey, widely known as the Brothers Grimm. The various Turkish translations of the fairy tale Snow White, produced by different authors, are compared, and the resulting different translations are evaluated in the context of the Skopos Theory. The translators who translated the fairy tales from the original German texts into Turkish are Kâmuran Şipal, Saffet Günersel, and Kemal Kaya. This study addresses the complexity of fairy tale translations, as well as the challenges encountered during the translation process. Particularly considering the purpose and target audience of the source text in the target language, difficulties may arise in translations for the reading audience of the fairy tale, primarily consisting of children. At this point, the Skopos theory, which focuses on the purpose of translation and the target audience, can be taken into account. The aim of the Skopos theory is to align the translation process with the specific purpose and target audience of the translation, so that the function of the translation is effectively fulfilled in the new context. It is important to identify the purpose of the translation. Is it a translation for children, aimed at conveying cultural values? The purpose-oriented analysis of texts allows for the recognition of the influence of the intended purpose on the translation. By examining how different purposes influence a translator’s linguistic and stylistic choices, one can better understand the factors that play a role in translation. This is especially important in an intercultural context, where misunderstandings should be avoided and cultural values accurately conveyed. This analysis could aim to examine how the translation has been adapted to the needs of a specific target audience, such as children. Another aim could be to analyze how cultural elements in the original text have been addressed in the translation to ensure their relevance for the target audience. One other aim could be to highlight the stylistic choices of the translator. How is the tone of the original maintained or altered? In this context, it also presents translation examples within the framework of Skopos theory, demonstrating that translators were successful in reaching the reader in the target language in some instances of translation.